Excision repair cross-complementation group 1 enzyme as a molecular determinant of responsiveness to platinum-based chemotherapy for non small-cell lung cancer - Mountzios, G.; Dimopoulos, M.-A.; Papadimitriou, C. (Biomarker Insights, 2008)
Although platinum-based chemotherapy remains the "standard" in advanced non small-cell lung cancer, not all patients-derive clinical benefit from such a treatment. Hence, the development of predictive biomarkers able to identify lung cancer patients who are most likely to benefit from cisplatin-based chemotherapy has become a scientific priority. Among the molecular pathways involved in DNA damage control after chemotherapy, the nucleotide excision repair (NER) is a critical process for the repair of DNA damage caused by cisplatin-induced DNA adducts. Many reports have explored the role of the excision repair cross-complementation group 1 enzyme (ERCC1) expression in the repair mechanism of cisplatin-induced DNA adducts in cancer cells. Using immunohistochemistry in resected tumors from patients included in the International Adjuvant Lung Cancer Trial, the study of important biomarkers showed that high ERCC1 protein expression was associated with improved survival in chemo-naïve patients. On the contrary, the benefit of adjuvant cisplatin-based chemotherapy was more profound in patients with low ERCC1 expression. In a prospective cohort studying mRNA expression in tumor biopsies from patients receiving customized therapy with cisplatin and gemcitabine depending on the molecular profile of the tumour, results showed that patients with low ERCC1 mRNA expression had a longer median survival compared to those with high expression. These data suggest the potent use of ERCC1 as a molecular predictor of clinical resistance to platinum-based chemotherapy in the adjuvant setting of NSCLC. Nevertheless, optimization of methodology, including standardization of technical procedures, as well as validation of ERCC1 protein expression in large prospective cohorts, seem necessary before any routine immunohistochemical validation of ERCC1 can be implemented in daily practice.
Keywords: Biomarkers; ERCC1; Non small-cell lung cancer; Platinum-based chemotherapy; Predictive